A STEREOCONTROLLED APPROACH TO 1-BETA-METHYLCARBAPENEM - Davies, S; Hedgecock, C; Mckenna, J (1995)
Conjugate addition of lithium N-allyl-N-α-methylbenzylamide to chiral α,β-unsaturated esters is subject to double stereodifferentiation, the mismatched pair reaction allowing access to an intermediate for 1β-methylcarbapenem synthesis. © 1995.